Coupled field finite element analysis of pin-and-cap disk type insulator assembly. (1st January 2014) - Palhade, R.D.; Tungikar, V.B.; Dhole, G.M.; Kherde, Sanjay M.
Extensive research has been done throughout the world on the performance of outdoor insulators and insulator assembly, in the area of structural, thermal and electrical analysis. These effects, i.e., structural, thermal and electric have been studied on individual basis only. That is only one effect is considered, however in the real field these effects should be considered simultaneously for the complete analysis of insulator and insulator assembly since these three effects are present at the same time. In this paper, coupled field structural-thermal-electrical finite element simulations are carried out by using a commercially available software package, which allow quantifying the effects of insulator assembly on when structural, thermal and electrical load distribution are considered simultaneously. The structural, thermal and electrical results are obtained for a single 11 kV cap-and-pin type ceramic disc type insulator assembly are analysed and presented. It is observed that under normal working conditions of an insulator assembly the structural, thermal and electrical loads are found mutually coupled, but not going to affect the structural, thermal and electrical characteristics of an insulator assembly and its components.